(untitled) (Plant Tissue Culture and Biotechnology, 2020)
The present study was undertaken to establish a protocol for in vitro callusing of three Jatropha accessions, namely Metema, Adami Tulu and Shewa Robit from leaf explants. The medium supplemented with combination of 4.44 μM BAP and 4.52 μM 2,4-D resulted in maximum percentage of callus (100%) formed for all accessions. The maximum shoot regeneration (66.67%) from callus with 10.13 number of shoot was obtained from Shewa Robit in MS medum fortified with TDZ (2.27 μM ) and IBA (0.49 μM ). The presence of TDZ in the shoot regeneration medium has greater influence on the induction of adventitious shoot buds, whereas MS supplemented with BAP alone and combination with IBA did not induce shoot regeneration from callus culture. The results obtained in the present study would facilitate the high callus induction and regeneration responses in Jatropha for its improvement using biotechnological tools. Plant Tissue Cult. & Biotech. 30(1): 131-141, 2020 (June)